A Perspective on Emerging Therapeutic Interventions for COVID-19 - Torequl Islam, Muhammad; Nasiruddin, Md.; Khan, Ishaq N.; Mishra, Siddhartha Kumar; Kudrat-E-Zahan, Md.; Alam Riaz, Thoufiqul; Ali, Eunus S.; Rahman, M. Safiur; Mubarak, Mohammad S.; Martorell, Miquel; Cho, William C.; Calina, Daniela; et al. (Frontiers in Public Health, 2020)
Coronaviruses are enveloped positive-sense RNA viruses with an unusual large RNA genome and a unique replication mechanism, which are characterized by club-like spikes that protrude from their surface. An outbreak of a novel coronavirus 2019 infection has posed significant threat to the health and economies in the whole world. This article reviewed the viral replication, pathogenicity, prevention and treatment strategies. With a lack of approved treatment options for this virus, alternative approaches to control the spread of disease is in urgent need. This article also covers some management strategies which may be applied to this virus outbreak. Ongoing clinical studies related to possible treatments for COVID-19, potential vaccines, and alternative medication such as natural compounds are also discussed.